PEMBELAJARAN ASWAJA SEBAGAI BASIS KEKUATAN PENDIDIKAN KARAKTER CINTA TANAH AIR DI MI MA’ARIF SAMBENG BANTUL YOGYAKARTA - Alifatul Azizah Istiyani; Ahmad Shofiyuddin Ichsan; Samsudin (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
This research is motivated by the increasing number of young people who join Islamic organizations which sometimes conflict with national customs and traditions. Aswaja learning in schools has an important role to provide an understanding of the correct creed without overriding the values ??of nationalism. This research type is field research using qualitative methods with a case study approach. This research took place in Madrasah Ibtidaiyah Ma'arif Sambeng Bantul, Yogyakarta. Data collection was done by observations, interviews, and documentations, while data analysis used circular theory. The results of this research are: 1) implementation of Aswaja learning as the basis for the strength of character education at MI Ma'arif Sambeng, among others: a) habituation activities, b) intra-curricular activities, and c) extracurricular activities. 2) the implications of Aswaja learning as the basis for the strength of character education at MI Ma'arif Sambeng, among others: a) respect for hero services, b) choosing to travel domestically, and c) respect for national culture. 3) the relevance of Aswaja's learning as the basis for the strength of character education in love the homeland at MI Ma'arif Sambeng according to current conditions by formulating a basic national attitude through a balance between Ukhuwah Islamiyah, Ukhuwah Wathaniyah, and Ukhuwah Insaniyah which need to be instilled in students from an early age.